Estimation of the serial interval of monkeypox during the early outbreak in 2022. Issue 1 (3rd November 2022) - Guo, Zihao; Zhao, Shi; Sun, Shengzhi; He, Daihai; Chong, Ka Chun; Yeoh, Eng Kiong
Abstract: With increased transmissibility and novel transmission mode, monkeypox poses new threats to public health globally in the background of the ongoing COVID‐19 pandemic. Estimates of the serial interval, a key epidemiological parameter of infectious disease transmission, could provide insights into the virus transmission risks. As of October 2022, little was known about the serial interval of monkeypox due to the lack of contact tracing data. In this study, public‐available contact tracing data of global monkeypox cases were collected and 21 infector‐infectee transmission pairs were identified. We proposed a statistical method applied to real‐world observations to estimate the serial interval of the monkeypox. We estimated a mean serial interval of 5.6 days with the right truncation and sampling bias adjusted and calculated the reproduction number of 1.33 for the early monkeypox outbreaks at a global scale. Our findings provided a preliminary understanding of the transmission potentials of the current situation of monkeypox outbreaks. We highlighted the need for continuous surveillance of monkeypox for transmission risk assessment.